An organic anion template: a 24-nucleus silver cluster encapsulating a squarate dimer1. Issue 48 (18th June 2015) - Liu, Kuan-Guan; Chen, Su-Kun; Lin, Yu-Mei; Wang, Quan-Ming
<x xml:space="preserve">Abstract</x> An unprecedented organic anion templated silver cluster has been isolated, leading to unusual π–π interaction within the encapsulated squarate dimer.